2014
DOI: 10.5688/ajpe787138
|View full text |Cite
|
Sign up to set email alerts
|

Student Self-Screening for Methicillin-Resistant Staphylococcus Aureus (MRSA) Nasal Colonization in Hand Hygiene Education

Abstract: Objective. To determine the feasibility and effectiveness of adding a hand hygiene exercise in selfscreening for Methicillin-Resistant Staphylococcus Aureus (MRSA) nasal colonization to a health care delivery course for first-year pharmacy (P1) students. Design. About one month after students were trained in hand hygiene technique and indications, faculty members demonstrated how to self-screen for MRSA nasal colonization. Students were then asked to screen themselves during the required class time. Aggregated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Although there have been prior studies of clinical hygiene infection control behaviors among chiropractic students, 35,36 none has linked these behaviors to a health outcome, and none of the behaviors have been re-assessed in several years. Although there have been prior studies of MRSA nasal carriage in US health care students, [37][38][39][40][41][42] none that the author is aware of has specifically screened for postmatriculation infection history, though others have generally inquired about past MRSA infection. 42 This study sought to determine the rates of prematriculation and postmatriculation MRSA SSTI in a sample of chiropractic students and any association with hygiene-related behaviors and initiation of patient care.…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been prior studies of clinical hygiene infection control behaviors among chiropractic students, 35,36 none has linked these behaviors to a health outcome, and none of the behaviors have been re-assessed in several years. Although there have been prior studies of MRSA nasal carriage in US health care students, [37][38][39][40][41][42] none that the author is aware of has specifically screened for postmatriculation infection history, though others have generally inquired about past MRSA infection. 42 This study sought to determine the rates of prematriculation and postmatriculation MRSA SSTI in a sample of chiropractic students and any association with hygiene-related behaviors and initiation of patient care.…”
Section: Introductionmentioning
confidence: 99%
“…7,13,14 A pilot study in an occupied patient room in this hospital over a one-month period demonstrated that this low-cost, automated monitoring system successfully tracked hand-hygiene adherence. 7 The system relied on passive RFID tags (stickers) placed under the photo and name plate of ID tags.…”
Section: Designmentioning
confidence: 99%